Democracia e sociedade civil : a participação política como ampliação da democracia representativa em Norberto Bobbio - Marques, Eduardo Nunes (2018)
Democracy, according to Norberto Bobbio's thinking, can only be considered if it obeys minimum precepts that establish who can make political decisions and with what procedures, in a material context of respect for fundamental rights. However, the apparent triumph of the post-World War II democratic order in relation to the Western world does not mean that the democratic regime, particularly the representative one, does not present its vicissitudes, generally described by Bobbio as the revenge of personal interests or groups representation, in addition to the lack of transparency in the relations practiced by the State. The answers to this crisis of representation, especially the relation between pluralism and participatory democracy in the work of Norberto Bobbio, are the object of the present research. To do so, concepts about democracy and civil society are retaken to define how the latter can legitimately improve decision-making in a representative democratic regime, based on the exercise of democratic powers in other spheres, not merely the formal space of politics. What we want to demonstrate is that the improvement of the channels of political participation in civil society improves representative and institutional democracy.